The Efforts for Productivity and Income Improvement of Rice Farming Through the Use New Superior Variety (Case Study) - Arya, Nyoman Ngurah; Mahaputra, I Ketut; Suharyanto, Suharyanto (AGRARIS: Journal of Agribusiness and Rural Development Research, 2017)
Various efforts to increase rice production have been done in order to achieve rice self-sufficiency and food security, one of which is the creation of some New Superior Varieties (NSVs) of paddy. This study aimed to analyze the productivity, income, and efficiency of rice farming of New Superior Varieties, including Inpari 29, Inpari 31, and Inpari 32. This research was conducted on December 2014 until April 2015 in Subak Gubug I, Gubug village, as one of the centers of rice production in Tabanan Regency. The study involved 30 farmers who planted those three new superior varieties in 9.38 hectares of wet land area.Â  Each farmer used as replicates. Data were collected using interview and direct observation. Data was analyzed by Analysis of Variance (ANOVA). The results showed that Inpari 31 variety have the highest productivity, the highest revenue, the most efficient, and significantly different from the Inpari 29 and 32. Multiplication and dissemination of Inpari 31 variety to farmers can be done as soon as possible to increase rice production, achieve rice self-sufficiency and food security.